Effect of seeed cluster and gibberellic acid (GA3)on the gender development of salak (Salacca edulis reinw) - Razifah, Mohd Razali (Fakulti Agroteknologi dan Sains Makanan, 2011)
A series of experiments on growth and development of Salacca edulis REINW. were conducted in the greenhouse of Universiti Malaysia Terengganu (UMT) and in the field on undeveloped agriculture land (bris soil) in Tumpat, Kelantan. The nursery study was undertaken for six months followed by a field study for 24 months. In the nursery study, seeds were soaked in 0, 10, 50 and 100 ppm gibberellic acid (GA3) and planted in individual polybags according to their type of seed clusters which comprised one, two and three seeds per fruit. The polybags were placed under warm, moist and shady conditions to avoid stress due to dryness and over-watering. The seedlings were then left for six months in the greenhouse before they were transplanted into the field.